ANALISIS KEBIJAKAN PENGAMPUNAN PAJAK (STUDI WAJIB PAJAK BADAN DAN ORANG PRIBADI KOTA SURABAYA) - Siska Yulia Weny (Behavioral Accounting Journal, 2018)
Tax are the most potential source of Indonesia state revenues, tax will be used to development and improvement the economic of people in Indonesia. Many way to get tax revenue they are increasing the number of active taxpayers, increasing of taxpayers obedience. In fact taxpayers try to get a way for avoid tax payment. Tax payers hope there is a policy can solve problems taxation. In 2016 the goverment give taxpayers a policy which can help them, that is Tax Amnesty. The method in this research is qualitative interpretive method with phenomenology approach. collecting information technique in this research use observation, interview, and documentation. Informants in this study are 3 corporate taxpayers and 1 individual taxpayer. The results of this research are taxpayers who use policy of tax amnesty can more understanding about Tax amnesty, many positive impact for taxpayers who use the policy, and Tax Amnesty Policy been able to resolve the problem of taxpayers.